Methodological approaches to correcting writing errors in middle school students - Kozhakhmetova Aidana Talgatkyzy (European Research Materials, 2025)
In the modern world, which is increasingly becoming open and multilingual, learning foreign languages is becoming especially important. As a basis for successful communication in an international context, mastering a foreign language in educational institutions at all levels poses many challenges to teachers and students. Among them is the achievement of communicative competence, which requires not only mastering language knowledge and speech skills, but also developing the ability to effectively reflect on language at each stage of learning [1, 23]. The specificity of a foreign language as an academic subject creates objective difficulties for students related to its internal structure and the need for simultaneous development of language knowledge, speech skills and abilities. These difficulties are compounded by the presence of language and speech interference described by F. de Saussure, who distinguished between the abstract and universal nature of language and the individual, emotionally colored nature of speech [2, 134].